2002
DOI: 10.1002/jat.867
|View full text |Cite
|
Sign up to set email alerts
|

In vivo effect of 5‐ and 8‐methoxypsoralens and cimetidine on R,S‐warfarin metabolism in rat

Abstract: Several forms of cytochrome P-450 (CYP) metabolize R,S-warfarin in a regio- and enantioselective manner, therefore R,S-warfarin can be recognized as a metabolic probe for a number of CYP isoforms. We have applied a warfarin model in vivo in order to estimate the inhibitory properties of 5- and 8-methoxypsoralens on the activity of rat CYP isoforms. The area under the serum concentration versus time curve (AUC) values from time zero to 5 h for R- and S-warfarin and their metabolites were calculated. R,S-Warfari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…Subsequent exploration of the observations made in patients with studies in healthy volunteers showed that treatment with cimetidine caused a decrease of overall CYP activity, according to in vitro findings [9,10]. However, no specific effect on CYP3A4 activity in vivo was noted.…”
Section: Relative Changes In Overall Cyp (A) and Hepatic (Left) Andmentioning
confidence: 83%
See 1 more Smart Citation
“…Subsequent exploration of the observations made in patients with studies in healthy volunteers showed that treatment with cimetidine caused a decrease of overall CYP activity, according to in vitro findings [9,10]. However, no specific effect on CYP3A4 activity in vivo was noted.…”
Section: Relative Changes In Overall Cyp (A) and Hepatic (Left) Andmentioning
confidence: 83%
“…However, numerous studies have demonstrated a modulating effect of both cimetidine and omeprazole-and to a lesser extent ranitidineon several CYP isozymes, implicating a potential effect on bioavailability and clearance of CYP3A4 dependent immunosuppressants. Most of these studies have been done in vitro or ex vivo, which does not allow an easy extrapolation to clinical practice [9][10][11][12].…”
mentioning
confidence: 99%
“…However, a closely related substance, 4(5)-(benzylthiomethyl)-1H-imidazole (which has the structure of CC12 without the iodosubstituent), was reported to be a weak inhibitor of histamine synthesis (Swett and Yellin, 1970), and an inhibitor of microsomal drug oxidation (Wilkinson et al, 1974;Wilkinson et al, 1972). Interactions between imidazole-containing histamine antagonists and some cytochrome P-450 proteins are well known (Szutowski et al, 2002,Alves-Rodrigues et al, 1996. The modulation of a cytochrome P-450 protein by CC12 could be the basis for this drug's antianalgesic action, since a P-450 pathway has been implicated in supraspinal opioid analgesic signaling (Vaughan et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Initially, the analytical method of high-performance liquid chromatography (HPLC) with ultraviolet (UV) spectrum detection was used for the quantification of warfarin [68]. In these works, warfarin was isolated from plasma or serum by solid-phase extraction on a semipermeable surface guard column [6] or by liquid/liquid extraction with ice-cold acetonitrile [7] or with diethyl ether [8]. Although a 100  μ L [6, 7] or 1 mL aliquot of plasma [8] was used, such an analytical method was questionable due to low specificity and sensitivity of UV detection.…”
Section: Introductionmentioning
confidence: 99%
“…In these works, warfarin was isolated from plasma or serum by solid-phase extraction on a semipermeable surface guard column [6] or by liquid/liquid extraction with ice-cold acetonitrile [7] or with diethyl ether [8]. Although a 100  μ L [6, 7] or 1 mL aliquot of plasma [8] was used, such an analytical method was questionable due to low specificity and sensitivity of UV detection. Therefore, several methods of HPLC with mass spectrometry (MS) and HPLC with tandem mass spectrometry (MS/MS) have been developed for warfarin quantification in single-reaction monitoring mode [5, 9, 10] or multiple-reaction monitoring mode [4, 1113].…”
Section: Introductionmentioning
confidence: 99%